Village Government Performance in Distribution Services Direct Cash Assistance in Pesaku Village, West Dolo District Sigi Regency - Waris, Irwan; Alfianti, Winda; Susanti, Ani; Nuraisyah, Nuraisyah (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to determine the performance of village officials in realizing Good, Professional Performance and Satisfactory Service Quality to the community in Pesaku Village, West Dolo District, Sigi Regency in accordance with applicable regulations. The main theory used as a reference in this research is Agus Dwiyanto's theory, including; (1) Productivity, (2) Service Quality, (3) Responsiveness, (4) Responsibility (5) Accountability This research method uses a descriptive – qualitative approach. The location of this research was in Pesaku Village, West Dolo District, Sigi Regency, with 5 informants selected purposively. Data collection was carried out by conducting interviews, observation and documentation. Data analysis techniques using the Miles and Huberman interactive model. Based on the research results, the number of people receiving direct cash assistance does not match the existing data, the village government is also unable to provide optimal services because the quality provided by the village government is still very low, influenced by the responsibility aspect which is not yet running well because there are still tools villages that do not carry out discipline according to the rules so that the accountability of the village government is still very low so that optimal services to break the chain of poverty and improve the welfare of the village community have not been implemented optimally.